DINAMIKA EKONOMI-KULTURAL INDUSTRI PENERBITAN BUKU-BUKU ISLAM POPULER DI INDONESIA - Ridwan Muzir Ridwan Muzir (Universitas Islam Negeri Imam Bonjol Padang, 2014)
This paper explores the position of Islamic populer book in socio-cultural setting of contemporary Muslim inIndonesia. It focuses on how publishing industries placed the books they published in relation with muslimsociety at large. Here, the book will be talked as cultural goods as well as economic goods. By way of that, itwill be seen that it is the economic motive which drive the differentiation of Islamic popular book, in termof genre, reader, market segment and title. The concept of the field of cultural production from Bourdieuancultural sociology shows that in a field like Islamic popular book production, legitimation and consecrationas cultural capital are gained from the consumers as well as from the competitor. This cultural capital can beconversed into economic capital, which is in its turn can be conversed again into more cultural capital.